How Do Specific Nutritional Interventions (e.g., Enteral Nutrition, Protein Supplementation, Micronutrient Support) Affect Mortality, Length of Hospital Stay, and Recovery in Patients with Pneumonia? : A Systematic Review - Bayu Anggara H (International Medical Journal Corp. Ltd, 2026)
Introduction: Pneumonia remains a leading cause of morbidity and mortality worldwide, with malnutrition significantly exacerbating poor clinical outcomes. Despite growing interest in nutritional interventions, evidence regarding their specific effects on mortality, hospital stay, and recovery in pneumonia patients remains heterogeneous and inconclusive. Methods: This systematic review synthesized evidence from 57 studies evaluating nutritional interventions in pneumonia patients, including 12 randomized controlled trials, 6 systematic reviews/meta-analyses, and 39 observational studies. Studies were screened based on predefined criteria including primary pneumonia diagnosis, specific nutritional interventions, relevant clinical outcomes, and adult populations. Data extraction encompassed intervention characteristics, patient demographics, comparator groups, mortality, length of stay, and recovery indicators. Results: Early enteral nutrition initiated within 24-48 hours significantly reduced mortality (OR 0.45, 95% CI 0.21-0.95, p=0.038) and shortened hospital LOS by 3.54 days (p<0.00001). Each 30g/day increase in protein intake was associated with 24% reduced 60-day mortality (OR 0.76, p<0.001). Enteral nutrition demonstrated superior outcomes compared to parenteral nutrition across mortality (13.8% vs 27.1%, p=0.003), LOS (18.0 vs 28.0 days, p<0.05), and complication rates. High-protein feeding (1.8-2.2 g/kg/d) significantly attenuated muscle atrophy (13.97% vs 18.96%, p<0.001). Individualized nutritional programs reduced readmission by 77% (p=0.03) in malnourished elderly. Discussion: Nutritional interventions demonstrate clinically meaningful benefits when appropriately timed, dosed, and delivered via enteral routes. Heterogeneity in mortality findings reflects differential effects of intervention timing, nutritional adequacy thresholds, and baseline nutritional risk. Conclusion: Early enteral nutrition with adequate protein delivery should be standard care in hospitalized pneumonia patients. Future research should focus on optimal protein dosing, immunonutrition strategies, and post-discharge nutritional rehabilitation.